DINAMIKA KELEMBAGAAN KELOMPOK TANI HUTAN RAKYAT LAHAN KERING DI DESA TAMBAK UKIR KECAMATAN KENDIT KABUPATEN SITUBONDO - Bowo, Cahyoadi; Supriono, Agus; Hariyono, Kacung; Kosasih, Safari (Jurnal Sosial Ekonomi Pertanian, 2011)
Kabupaten Situbondo is one of Kabupaten in East Java province that frequently developes dry land of community forest, particularly on the community forest. Model of policy being applied is through reinforcement of community forest farmer group empowerement. However, there are still many obstacles for the implementation in the real field. This condition is believed to be affecting by the level of group dynamics at the farmer group institutional as one of the factor. Being interested on this phenomenon, then research team was attracted to conduct the study in order to find out about the group dynamics on those several dry land smallholder groups. The research was conducted at Village of Tambak Ukir-Kecamatan Kendit. Method of analysis being used is interval class. The research result showed that one of the farmer group has medium dynamic (Jaya Makmur), then two other groups has low dynamic (Karya Tani and Suka Maju), and one of group has very low dynamic (Gua Kembar). Jaya Makmur farmer group is more developed that three other farmer groups because it has dimension objectives of group, group compactness, group structure, duty function of group, development and maintenance of group, situation of group, effectiness of group and also group pressure that relatively more dynamic. Key Words : dry land, community forest, farmer group, group dynamics